2002
DOI: 10.1074/jbc.m108341200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Protein Interactions at the Nicotinic Acetylcholine Receptor

Abstract: The structural and functional properties of reconstituted nicotinic acetylcholine receptor membranes composed of phosphatidyl choline either with or without cholesterol and/or phosphatidic acid have been examined to test the hypothesis that receptor conformational equilibria are modulated by the physical properties of the surrounding lipid environment. Spectroscopic and chemical labeling data indicate that the receptor in phosphatidylcholine alone is stabilized in a desensitizedlike state, whereas the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 33 publications
4
106
0
Order By: Relevance
“…The correlation between bulk lipid ordering and nAChR function is not obvious based on previous experimental studies 9,50 . The nAChR in 3:2 POPC/POPA appears to be predominately in a resting like state that is capable of undergoing agonist-induced desensitization.…”
Section: Lipid Orderingmentioning
confidence: 94%
See 3 more Smart Citations
“…The correlation between bulk lipid ordering and nAChR function is not obvious based on previous experimental studies 9,50 . The nAChR in 3:2 POPC/POPA appears to be predominately in a resting like state that is capable of undergoing agonist-induced desensitization.…”
Section: Lipid Orderingmentioning
confidence: 94%
“…The prepared large ternary lipid patch has the 3:1:1 molar ratio of POPC, POPA, and CHOL to mimic the composition requirement of the lipid mixture for functional nAChRs 9 . Sodium and chloride ions were added into the system by replacing water molecules to produce ionic concentrations of 150 mM.…”
Section: System Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Different experimental approaches have revealed dynamic information about agonist-induced conformational changes of the pore forming domains (M1 and M2) (8,(11)(12)(13)(14). It is noteworthy that a recent study suggested that there is no significant movement of the pore lining domains during channel activation of the AChR (14).…”
mentioning
confidence: 99%